First record of the family Stephanidae (Hymenoptera: Stephanoidea) for the fauna of Saudi Arabia, with the description of a new species - Soliman, Ahmed M.; Gadallah, Neveen S.; Dhafer, Hathal M. Al (Zootaxa, 2017)
The family Stephanidae (Hymenoptera: Stephanoidea) is recorded for the first time from Saudi Arabia. It is represented by two species belonging to the genus Foenatopus, F. bisignatus Aguiar & Jennings, 2010 and F. cf. turcomanorum (Semenov, 1891). A new species, Profoenatopus bimaculatus sp. nov. from Asir region is also described and illustrated.